2010 International Forum on Information Technology and Applications 2010
DOI: 10.1109/ifita.2010.225
|View full text |Cite
|
Sign up to set email alerts
|

An Integration Management System for Managing Business Continuity, Records and Knowledge

Abstract: Developing an integration management system for business continuity, records and knowledge (IMS of BRK) is beneficial to the collaboration, optimization and innovation of business continuity management system (BCMS), records management system (RMS) and knowledge management system (KMS) for organization. Comprehensive research and development requirements along with a cogent framework, however, have not been proposed for integrating three of them, which were proposed independently. Based on situational analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…With our limitations in working, we realize that this study still has many shortcomings but some important notes that we can suggest as further research are the addition of new features in SEMARAK which are integrated with attendance systems, teleconferencing, virtual reality, videographers, etc. (Bustelo & García-Morales 2008;An et al, 2010;Boukar & Muslu, 2013;XU et al, 2019), It is hoped that with the addition of features that have been observed previously, it can work better for SEMARAK.…”
Section: Resultsmentioning
confidence: 92%
“…With our limitations in working, we realize that this study still has many shortcomings but some important notes that we can suggest as further research are the addition of new features in SEMARAK which are integrated with attendance systems, teleconferencing, virtual reality, videographers, etc. (Bustelo & García-Morales 2008;An et al, 2010;Boukar & Muslu, 2013;XU et al, 2019), It is hoped that with the addition of features that have been observed previously, it can work better for SEMARAK.…”
Section: Resultsmentioning
confidence: 92%
“…Application of Big Data technology in the digital transformation of enterprise business management [9]. The application of Big Data technology in enterprise management has brought largescale data, and has the characteristics of large volume, fast speed, diversity and authenticity [10]. In the current background of technology development, enterprise managers can through the Big Data technology platform and system ,in order to get a job and the decision-making needs for the corresponding data, due to the characteristics of Big Data technology, objective, scientific and accurate data source, the sources including enterprise internal management statements, market information, competitive enterprise information in the same industry, these data through Big Data, information and other technology for processing, calculation, analysis and induction.…”
Section: Introductionmentioning
confidence: 99%